Towards a grounded theory of how and why founders vary in their scaling approaches: Alleviating period poverty - Bhogal, Nishana (Graduate School of Business (GSB), 2023)
I conducted a qualitative, inductive field study of nine founders alleviating period poverty. Iterating between data collected and analysed and literature, I adjusted my research question based on the data themes identified, enabling me to answer how and why prosocial founders vary in their scaling approaches in the context of extreme poverty. I conducted the study in South Africa, a nation characterised by high levels of inequality and widespread poverty, with women and children often bearing the brunt of these challenges. Although all founders engaged in alleviating period poverty, this study revealed that their responses were distinct, either person- or problem-oriented. Founders responding with the former endeavoured to broadly enhance the beneficiaries' lives, while those with the latter remained narrowly focused on alleviating period poverty. These differences were rooted in the founders' perception of the beneficiaries, which served as a powerful motivator for entrepreneurial action. My main contributions are to the literature on scaling ventures oriented towards addressing social challenges. I contribute by introducing two distinct prosocial founder responses, person- and problem-oriented. Moreover, I develop theory that explains the motivation for these distinct responses. In addition, prior literature emphasises that the founders' degree of embeddedness shapes scaling outcomes. Instead, I demonstrate that founders may engage with embedded actors, external to the founders' ventures, to shape scaling outcomes. In addition, this study contributes to the literature on entrepreneurship in impoverished contexts. I demonstrate that prosocial founders engaged in ostensibly similar efforts may play very different roles in engendering social capital that connects actors from impoverished and resource-rich contexts. Through this social capital, beneficiaries accessed additional resources. Creating such social capital is crucial in contexts with high levels of inequality; since it represents initial social capital across different social classes.